Photothermal Enhanced and Tumor Microenvironment Responsive Nanozyme for Amplified Cascade Enzyme Catalytic Therapy. Issue 7 (9th December 2022) - Zhu, Yang; Pan, Yuanbo; Guo, Zhengxi; Jin, Duo; Wang, Wenyu; Liu, Manman; Zong, Mingxi; Zheng, Xinwei; Wu, Yun; Wang, Lulu; Tian, Changlin; Cheng, Junjie; et al.
Abstract: Nanocatalysts, a class of nanomaterials with intrinsic enzyme‐like activities, have been widely investigated for cancer catalytic therapy in recent years. However, precise construction of nanocatalysts with excellent enzyme catalytic activity and biosafety for tumor therapy still remains challenging. Here, a biodegradable nanocatalyst, PEGylated Cu x Mn y S z (PCMS), is reported that can promote cascade catalytic reactions in tumor microenvironment (TME) while confining off‐target side effects on normal tissues. PCMS not only catalyzes the cascade conversion of endogenous hydrogen peroxide (H2 O2 ) to oxygen (O2 ) via catalase‐like activity and then to superoxide radical (·O2 − ) via oxidase‐like activity in the TME, but also effectively depletes intracellular glutathione via glutathione oxidase‐like activity. The cascade catalytic reactions, by taking advantage of high H2 O2 level in tumor cells, result in an enhanced enzyme catalytic effect in generation of ·O2 − . More importantly, PCMS exhibits prominent photothermal effect under NIR‐II 1064 nm laser irradiation that can further enhance chemodynamic therapy (CDT) efficacy in tumors. In addition, the biodegradation in TME and excellent photothermal effect of PCMS are beneficial to magnetic resonance imaging, photoacoustic imaging and infrared thermal imaging, resulting in tracing the fate of PCMS in vivo. This study provides a new tool for rational design of TME‐responsive nanocatalysts with high biocompatibility for tumor catalytic therapy. Abstract : A PEGylated Cu x Mn y S z (PCMS) nanozyme possessing excellent catalase‐like, oxidase ‐like, and glutathione oxidase‐like activities is constructed. PCMS catalyzes cascade conversions of endogenous H2 O2 to O2 and then to ·O2 ‐, and depletes intracellular glutathione in the tumor microenvironment. PCMS also exhibits a profound photothermal effect under 1064 nm laser irradiation, which enhances the catalytic activities for tumor therapy.